Design of a Smart Thermal Grid in the Wilhelmsburg district of Hamburg : Challenges and approaches - Peter Lorenzen and Philipp Janßen and Michael Winkel and Dörte Klose and Paul Kernstock and Joel Schrage and Franz Schubert (Energy procedia, 2018)
The paper presents the design of a smart thermal grid in the Wilhelmsburg district of Hamburg. It is emphasized how technical and economical concepts are cross-linked and how district heating systems can become more flexible and efficient by focusing on the whole lifecycle process from customer acquisition over implementation up to operation. Technical concepts for centralized and decentralized generation, grid design and consumer integration are shown. Currently some of these are in the process of implementation, e.g. a grid coupling point, power house expansion, and flexible customers using 3-pipe connections and smart substations.
Keywords: Efficiency; Flexible Operation; Renewable Heat Generation; Smart Thermal Grid